Handbook of regional and urban economics regional eocnomics - Arrow, Kenneth J (Ed.); Intriligator, Michael D (Ed.) (Amsterdam Elsevier, 2000)
Handbook of regional and urban economics is in three volumes The first volume contents are-regional economics,regional andeconomic development and policy.Volumes two contents are-Urban economics,locational analysis,specfic urban markets,urbangovernment be
V2.is edited by Edwin S mills.
Keywords: REGIONAL ECONOMICS-HANDBOOKS, MANUALS, ETC; URBAN ECONOMICS-HANDBOOKS, MANUALS ETC